1998
DOI: 10.1136/gut.42.6.850
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress: an important phenomenon with pathogenetic significance in the progression of acute pancreatitis

Abstract: Background-Reactive oxygen species and related oxidative damage have been implicated in the initiation of acute pancreatitis. Changes in these parameters during disease progression merit further investigation. Aims-To evaluate changes and the clinical relevance of superoxide radicals, endogenous antioxidants, and lipid peroxidation during the course of acute pancreatitis. Patients and methods-Superoxide radicals (measured as lucigenin amplified chemiluminescence), ascorbic acid, dehydroascorbic acid, tocophero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 35 publications
(28 reference statements)
6
111
0
2
Order By: Relevance
“…This results in edema, vascular damage, hemorrhage and cell death (18,19). In addition to oxidative stress (20) and calcium overload (21), hypotension (22) and low acinar pH (23) contribute to these initiation processes. After initial production of active pancreatic enzymes, local cell death and systemic inflammation ensue.…”
Section: Introductionmentioning
confidence: 99%
“…This results in edema, vascular damage, hemorrhage and cell death (18,19). In addition to oxidative stress (20) and calcium overload (21), hypotension (22) and low acinar pH (23) contribute to these initiation processes. After initial production of active pancreatic enzymes, local cell death and systemic inflammation ensue.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that OS is higher in patients with AP than in healthy volunteers or patients with acute abdominal processes other than AP (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and in patients with severe AP (SAP) it is higher than in those with mild AP (MAP) (8)(9)(10)(11)(12)(13)(14)16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress has been implicated in the development of acute pancreatitis in diverse animal experimental models, including fatty acid infusion, ischaemia, pancreatic duct obstruction, gallstone pancreatitis and alcohol ingestion, 60,[62][63][64] and measured in patients with mild and severe acute pancreatitis. 65 Previously, we have demonstrated the vital role of Ca 2 þ on MPTP opening in pancreatic acinar cell apoptosis induced by the oxidant menadione. 10 Crucially, the Ca 2 þ chelator BAPTA prevented both menadione-induced repetitive cytosolic Ca 2 þ spikes and apoptosis, instigated via the intrinsic apoptotic pathway.…”
mentioning
confidence: 98%